Aktivitas Orang Tua Dalam Menanamkan Nilai-nilai Agama Islam Pada Anak Usia 6-8 tahun Di Dusun Perasak Desa Gapura Tahun 2022 - Ranisa, Ranisa (Lunggi Journal, 2024)
The results of the research show that the effectiveness of vocational training centers in improving community skills in 2021 has not been maximally effective. This study concludes that there are still many implementation efforts that have not achieved success, the types of training are limited, the procedures applied are still not optimal, the material provided is still lacking and the facilities do not meet standards. Obstacles faced by the Sambas district vocational training center in improving skills can be seen from internal factors, namely participants who have different backgrounds, lack of teaching staff, training equipment that does not meet standards, the application of the curriculum has not yet reached the textile industry stage and limited training budgets. In terms of external factors, there is no devaluation of the pre-training participants.